An untapped resource: Treatment as a tool for revealing the nature of cognitive processes - Nickels, L.; Kohnen, S.; Biedermann, Britta (2010)
This paper focuses on the role of treatment in cognitive neuropsychological research, arguing that treatment for cognitive impairments should be viewed as a powerful methodology for developing, evaluating, and extending cognitive theories. We suggest that the key aim of cognitive neuropsychology should be characterized as the use of data from the investigation and treatment of individuals with cognitive disorders to develop, evaluate, and extend theories of normal cognition. To support this assertion, this paper discusses examples of how treatment studies have informed theory. The major methodological tool is generalization logic, both generalization across items and generalization across tasks. However, an alternative is to use case series methodology to test predicted correlations between particular cognitive skills and response to treatment. These methods enable explicit testing of a theory or discrimination between theories, focusing on the nature of cognitive representations, the architecture of the cognitive system, and the acquisition of cognitive skills. © 2011 Psychology Press.